Effects of 5′,8′-Cyclo-2′-Deoxypurines on the Base Excision Repair of Clustered DNA Lesions in Nuclear Extracts of the XPC Cell Line - Julia Kaźmierczak-Barańska (MDPI AG, 2021)
Clustered DNA lesions (CDL) containing 5′,8-cyclo-2′-deoxypurines (cdPus) are an example of extensive abnormalities occurring in the DNA helix and may impede cellular repair processes. The changes in the efficiency of nuclear base excision repair (BER) were investigated using (a) two cell lines, one of the normal skin fibroblasts as a reference (BJ) and the second from Xeroderma pigmentosum patients’ skin (XPC), and (b) synthetic oligonucleotides with single- and double-stranded CDL (containing 5′,8-cyclo-2′-deoxyadenosine (cdA) and the abasic (AP) site at various distances between lesions). The nuclear BER has been observed and the effect of both cdA isomers (5′R and 5′S) presence in the DNA was tested. CdPus affected the repair of the second lesion within the CDL. The BER system more efficiently processed damage in the vicinity of the ScdA isomer and changes located in the 3′-end direction for dsCDL and in the 5′-end direction for ssCDL. The presented study is the very first investigation of the repair processes of the CDL containing cdPu considering cells derived from a Xeroderma pigmentosum patient.